Grounding Optimization Using Soil Resistivity and Parallel Rod Electrodes for a 3 m³/s Flood Pump - Lilin Elvira Ruliawati; Lusia Rakhmawati (CV. Creative Tugu Pena, 2026)
A critical component of flood pump electrical installations is the grounding system, as it provides a low-impedance path for leakage current, fault current, and transient overvoltage to flow into the earth. The grounding system at the Jagir Kalimir Flood Pump Station in Surabaya was optimized for a pump with a capacity of 3 m³/s by calculating in-situ soil resistivity using the Wenner method and implementing a parallel electrode design. The initial grounding resistance was 13.31 Ω, exceeding the PUIL 2011 limit of ≤5 Ω, indicating that it was insufficient to dissipate fault current effectively. The Wenner four-probe method, with probe spacings of 1.0 m, 1.5 m, and 2.5 m, yielded an average apparent soil resistivity of approximately 6.48 ± 0.19 Ωm. This result indicates that the soil had low apparent resistivity, which is consistent with wet soil conditions during the rainy season. However, a detailed geotechnical classification was not included in this study. Before optimization, field measurements recorded a leakage current of 312 mA and an average of four protection trips per week in the low-voltage main distribution panel (LVMDP) and control panel, indicating the presence of electromagnetic induction and arcing. The optimization was implemented using two vertical electrode rods, each approximately 2.5 m long, installed with a spacing of 2.5 m between them and connected to the main distribution panel through a 20 m grounding conductor. After optimization, the grounding resistance decreased from 13.31 ± 0.06 Ω to 1.11 ± 0.02 Ω, representing a reduction of 91.66 ± 0.15 percentage points. Dwight's analysis predicted an ideal grounding resistance of 1.12 Ω for the proposed configuration, while the measured value obtained using the two parallel rods showed a deviation of approximately 1.04%, demonstrating close agreement with the analytical prediction. However, the limitation of mutual resistance between the electrodes was still recognized. After optimization, the leakage current decreased to 28 mA, and no protection trips, looping, or arcing were recorded during approximately one week of observation. The novelty of this research lies in the combination of Wenner soil resistivity profiling at the specific site, electrode dimension selection based on Dwight's analysis, and field validation for the grounding system of a flood pump electrical installation.